2018
DOI: 10.1021/acs.cgd.8b01137
|View full text |Cite
|
Sign up to set email alerts
|

Role of Side Chains in the Solid State Assembly of Cyclic Peptoids

Abstract: Formation of stable porous frameworks based on cyclic peptoids can be triggered by strategic choice of appropriate side chains. In this contribution we demonstrate that substitution of distal propargyl side chains with methoxyethyl groups in a fully propargylated cyclic octamer peptoid (cyclo-(Npa)8 1) greatly improves the solid state stability inducing permanent one-dimensional porosity of the compound (cyclo-[(NPa)3(Nme)]2 2, Npa = N-(propargyl)­glycine, Nme = N-(methoxyethyl)­glycine). In both compounds the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…In (cyclo)peptoids, CH 2 ⋅⋅⋅OC hydrogen bonds [3] take the place of ordinary NH⋅⋅⋅OC bonds in peptides. The intermolecular CH 2 ⋅⋅⋅OC interactions trigger the solid state assembly of unexpected supramolecular architectures and porous structures reported by our group [4–7] …”
Section: Figurementioning
confidence: 77%
See 2 more Smart Citations
“…In (cyclo)peptoids, CH 2 ⋅⋅⋅OC hydrogen bonds [3] take the place of ordinary NH⋅⋅⋅OC bonds in peptides. The intermolecular CH 2 ⋅⋅⋅OC interactions trigger the solid state assembly of unexpected supramolecular architectures and porous structures reported by our group [4–7] …”
Section: Figurementioning
confidence: 77%
“…The intermolecular CH 2 •••OC interactions trigger the solid state assembly of unexpected supramolecular architectures andp orouss tructures reported by our group. [4][5][6][7] In ar ecent contribution, we have shown how the dramatic conformational changes of compound 1 (a cyclic hexapeptoid decorated with four propargyl and two methoxyethyl side chains, Scheme 1) allow for the adsorption and releaseo fa ce-tonitrilem olecules through as ingle-crystal-to-single-crystal transformation. [4] We also demonstrated that the conformational flexibility of compound 1 leads to several solvatomorphs, as reported in Scheme 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Very rencently, Izzo and coworkers demonstrated that the presence of distal propargyl side chains with methoxyethyl groups can effectively enhance the stability in a fully propargylated cyclic octamer, which gave rise to permanent 1D porosity . This study demonstrated that the inter‐chain interactions are not only important for self‐assembly of linear polypeptoid, like nanosheet, but also vital for crystallization of cyclic polypeptoids.…”
Section: Crystallization and Self‐assembly Of Polypeptoid Polymersmentioning
confidence: 86%
“…In more than ten years from the brilliant work by Kent Kirshenbaum and co‐workers, cyclic peptoids gained the status of key bioactive/biomimetic agents, efficient catalysts, promising supramolecular building‐blocks, and rigid scaffold/topological templates …”
Section: Introductionmentioning
confidence: 99%